Designing and validating a questionnaire to evaluate knowledge, attitude and practise of leadership among medical doctors - Dinakren, Balashanmugam (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Leadership by healthcare professionals is essential in healthcare settings as it improves clinical outcomes in patients and cost-efficient care. This study aims to develop and determine validity and reliability of the Knowledge, Attitude and Practise questionnaire that evaluate leadership among medical doctors in Malaysia (KAP-LM). The KAP-LM was developed with 16 knowledge, 14 attitude and 14 practise items on medical leadership. The instrument then was tested for content and face validity followed by construct validity and internal consistency reliability. The questionnaire was completed by 180 medical officers from Hospital Selayang, Selangor and International Islamic University Malaysia Medical Centre, Pahang. Content validity and face validity of the KAP-LM were determined by six experts and 15 medical doctors respectively. Two factors were identified through factor analysis in construct validity. All the item in KAP-LM is reliable based on its internal consistency reliability with overall α=0.792. Inter correlation between dimensions of attitude and practise section in KAP-LM presented with good r-values ranging from 0.308 ~ 0.698. Evidence of validity and reliability of the KAP-LM (12 knowledge, 12 attitude, 12 practise items) have been obtained. The KAP-LM instrument can be used to assess KAP of leadership among medical doctors in Malaysia.